Pengaruh Status Sosial Ekonomi Keluarga Terhadap Prestasi Belajar Siswa - Diva Putri Suharbiani; Agus Lestari (Sinergi : Jurnal Ilmiah Multidisiplin, 2025)
This study aims to understand how family socio-economic conditions affect students' academic achievement through a literature review. The analysis was conducted by reviewing various scientific sources, such as national and international journals, academic articles, proceedings, and books published between 2015 and 2025, which are relevant to this topic. The findings show that socio-economic status, as seen from parents' income, education level, and occupation, has a strong relationship with students' academic achievement. Parents with adequate income can generally provide better learning facilities and financial support, which motivates children to study more. Additionally, parents' education plays a role in providing academic guidance at home and creating a family interaction pattern that supports children's cognitive development. This study also found that students' motivation and self-confidence are important factors that bridge the relationship between socio-economic conditions and academic outcomes. However, achievement gaps between students from different socio-economic backgrounds are still often found, especially in educational environments with high social stratification. Overall, this study emphasizes that family socio-economic conditions play an important role in shaping students' learning outcomes, both directly and through psychological factors and supportive learning environments. Keywords: Socio-economic status; parents' income; parents' education; academic achievement; learning motivation; literature review.   Abstrak Penelitian ini bertujuan untuk memahami bagaimana kondisi sosial ekonomi keluarga memengaruhi prestasi belajar siswa melalui studi literatur. Analisis dilakukan dengan meninjau berbagai sumber ilmiah, seperti jurnal nasional dan internasional, artikel akademik, prosiding, serta buku yang diterbitkan antara tahun 2015–2025 dan relevan dengan topik ini. Hasil kajian menunjukkan bahwa status sosial ekonomi yang dilihat dari pendapatan, tingkat pendidikan, dan jenis pekerjaan orang tua memiliki hubungan yang kuat dengan prestasi belajar siswa. Orang tua dengan pendapatan yang memadai umumnya dapat menyediakan fasilitas belajar yang lebih baik dan dukungan finansial yang membuat anak lebih termotivasi untuk belajar. Selain itu, pendidikan orang tua juga berperan dalam memberikan bimbingan akademik di rumah serta menciptakan pola interaksi keluarga yang mendukung perkembangan kognitif anak. Kajian ini juga menemukan bahwa motivasi dan kepercayaan diri siswa menjadi faktor penting yang menjembatani hubungan antara kondisi sosial ekonomi dan capaian akademik. Meski begitu, kesenjangan prestasi antara siswa dari berbagai lapisan sosial ekonomi masih sering dijumpai, terutama di lingkungan pendidikan dengan tingkat stratifikasi sosial yang tinggi. Secara keseluruhan, penelitian ini menegaskan bahwa kondisi sosial ekonomi keluarga memegang peran penting dalam membentuk hasil belajar siswa, baik secara langsung maupun melalui faktor psikologis dan lingkungan belajar yang mendukung. Kata Kunci: Status sosial ekonomi; pendapatan orang tua; pendidikan orang tua; prestasi belajar; motivasi belajar; literatur review.